Letter from Robert Chick - Robert Chick:::::: (1966)
A letter from the Committee to Re-Elect Governor Brown instructs county chairmen to respond quickly and aggressively to statements made by Ronald Reagan and other Republican spokesmen. Emphasizing lessons learned from the primary, it calls for immediate rebuttals to any false charges or distortions during the general election campaign. County leaders are directed to monitor speeches and television appearances, record exact quotes, and relay them promptly to campaign headquarters so responses can be issued within hours. The letter also recommends issuing follow-up statements from local supporters and coordinating closely with newly established media "monitors" in Los Angeles and San Francisco.